Monitoring and Evaluation of the Investment Attractiveness of the Region - Vladimir MYAKSHIN; Alexander PLASTININ; Tatyana PES'JAKOVA (Zenodo, 2015)
The authors have designed a balanced system of criteria to be applied when evaluating the investment attractiveness of Arkhangelsk Region, which enables the analysis of all the aspects of investment attractiveness and determine ways to enhance it. Applied to the investment attractiveness analysis, the balanced evaluation methodology enables identification of the region’s key challenges, as well as the priorities of its investment policy that target to enhance investment attractiveness and better balanced economic growth. This may contribute to scientific relevancy of the regulatory actions being undertaken by the government to improve investment climate at all levels – macro-level and meso-level.